Proceedings of the Second Workshop on Economics and Natural Language Processing 2019
DOI: 10.18653/v1/d19-5107
|View full text |Cite
|
Sign up to set email alerts
|

Complaint Analysis and Classification for Economic and Food Safety

Abstract: Governmental institutions are employing artificial intelligence techniques to deal with their specific problems and exploit their huge amounts of both structured and unstructured information. In particular, natural language processing and machine learning techniques are being used to process citizen feedback. In this paper, we report on the use of such techniques for analyzing and classifying complaints, in the context of the Portuguese Economic and Food Safety Authority. Grounded in its operational process, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Decision Support Systems. Many NLP systems have been developed to process text data (such as records, reports, scientific papers, and social media posts) to assist in making highly critical decisions, in domains like healthcare (Bampa and Dalianis, 2020;Mascio et al, 2020;Feng et al, 2020;Proux et al, 2009), finance (Kogan et al, 2009;Wang et al, 2013), business and management (Dong and Wang, 2015;Assawinjaipetch et al, 2016;Filgueiras et al, 2019), and legislation (Rabelo et al, 2019;Soh et al, 2019;Shaffer and Mayhew, 2019). Our work proposes the first decision support system to process nursing/midwifery complaints.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Decision Support Systems. Many NLP systems have been developed to process text data (such as records, reports, scientific papers, and social media posts) to assist in making highly critical decisions, in domains like healthcare (Bampa and Dalianis, 2020;Mascio et al, 2020;Feng et al, 2020;Proux et al, 2009), finance (Kogan et al, 2009;Wang et al, 2013), business and management (Dong and Wang, 2015;Assawinjaipetch et al, 2016;Filgueiras et al, 2019), and legislation (Rabelo et al, 2019;Soh et al, 2019;Shaffer and Mayhew, 2019). Our work proposes the first decision support system to process nursing/midwifery complaints.…”
Section: Related Workmentioning
confidence: 99%
“…Hence, large neural network models do not always outperform classic featurerich models and careful model selection is often necessary. For example, Filgueiras et al (2019) found that, in an economic activity classification task, the SVM (Cortes and Vapnik, 1995) with TF-IDF (Salton and Buckley, 1988) representations performed better than an LSTM network (Hochreiter and Schmidhuber, 1997). On the other hand, Assawinjaipetch et al (2016) and Mullenbach et al (2018) showed that in complaint and clinical classification tasks, RNNs (Cho et al, 2014) or CNNs (Kim, 2014) with pre-trained word2vec embeddings (Mikolov et al, 2013) outperformed the classic machine learning models with bag-of-words representations.…”
Section: Related Workmentioning
confidence: 99%
“…Decision Support Systems. Many NLP systems have been developed to process text data (such as records, reports, scientific papers, and social media posts) to assist in making highly critical decisions, in domains like healthcare (Bampa and Dalianis, 2020;Mascio et al, 2020;Proux et al, 2009), finance (Kogan et al, 2009;Wang et al, 2013), business and management (Dong and Wang, 2015;Assawinjaipetch et al, 2016;Filgueiras et al, 2019), and legislation (Rabelo et al, 2019;Soh et al, 2019;Shaffer and Mayhew, 2019). Our work proposes the first decision support system to process nursing/midwifery complaints.…”
Section: Related Workmentioning
confidence: 99%
“…Hence, large neural network models do not always outperform classic featurerich models and careful model selection is often necessary. For example, Filgueiras et al (2019) found that, in an economic activity classification task, the SVM (Cortes and Vapnik, 1995) with TF-IDF (Salton and Buckley, 1988) representations performed better than an LSTM network (Hochreiter and Schmidhuber, 1997). On the other hand, Assawinjaipetch et al (2016) and Mullenbach et al (2018) showed that in complaint and clinical classification tasks, RNNs or CNNs with pre-trained word2vec embeddings (Mikolov et al, 2013) outperformed the classic machine learning models with bag-of-words representations.…”
Section: Related Workmentioning
confidence: 99%
“…Different from existing complaint-related work [6,7,21] that regards every single complaint text as independent, our corpus contains a hierarchical relationship between clauses and paragraphs. Therefore, except for categorical statistics, we further explore the distribution and relation of clauses in specific paragraph.…”
Section: Dataset Analysismentioning
confidence: 99%